Budget Impact Analysis of Hypertonic Saline Inhalations for Infant Bronchiolitis: The Colombian National Health System Perspective (2022)
ABSTRACT: Objectives: Nebulized 3% hypertonic solution (HS) is associated with lower total cost and higher quality-adjusted life-years. Nevertheless, the expected budget impact of this drug had not been explicitly estimated. The aim of this study was to evaluate the budget impact of 3% HS in the treatment of acute bronchiolitis in Colombia. Methods: A budget impact analysis was performed to evaluate the potential financial impact of the use of 3% HS. The analysis considered a 4-year time horizon and a Colombian national health system perspective. The incremental budget impact was calculated by subtracting the cost of the new treatment, in which 3 % HS (added to humidified oxygen) was reimbursed, from the cost of the conventional treatment without 3 % HS (only humidified oxygen or adrenaline nebulization). Univariate 1-way sensitivity analyses were performed. Results: In the base-case analysis, the 4-year costs associated with HS and non-3% HS were estimated to be $47 792 230 and $53 312 832, respectively, indicating savings for Colombian national health system equal to $5 520 602 if HS is adopted for the routine management of patients with acute bronchiolitis. This result was robust in univariate 1-way sensitivity analysis. Conclusion: HS was cost saving in emergency settings for treating infants with acute bronchiolitis. This evidence can be used by decision makers in Colombia to improve clinical practice guidelines and should be replicated to validate their results in other middle-income countries.